Library Staffing in the Republic of Buryatia - E. A. Kuchmurukova (Библиосфера, 2025)
In recent years, there has been a difficult personnel situation in the library and information sphere. The obsolescence of personnel against the background of the lack of young professionals, an increase in the number of employees with non-core education and the outflow of library-educated workers to other industries are only a small part of the problems faced by the management of many libraries when forming their staff. Of particular concern is the situation in libraries of educational institutions and other organizations outside the jurisdiction of the Ministry of Culture, where the role of librarian is often performed by an employee who has a rather vague idea of his work. At the same time, the lack of a holistic picture across the entire library network does not allow a comprehensive approach to the study of existing problems and identify ways to solve them. The purpose of the article is to study the personnel situation in the libraries of Buryatia, determining the role of the university in staffing the industry. As a result, the characteristics of the library network of Buryatia, library staff were presented, the role of the East Siberian State Institute of Culture in training specialists for the library and information sphere of the region was outlined, the main problems were identified, the analysis of which will allow adjusting the joint work of libraries and universities to provide the industry with personnel.